Estandarización del proceso de soldadura del modelo Great Wall Motor Wingle 7 en la planta de ensamblaje de vehículos CIAUTO CIA. LTDA. - Guangasig Chango, Claudio David (2020)
The Ciauto Cia. Ltda. vehicle assembly plant which is the fourth assembly plant in the country, focused on the enrichment of the productive chain with national suppliers of auto parts and supplies for the manufacture of the vehicle. The Ciauto plant is located in Ambato city, Unamuncho parish, Conde neighborhood, Within the welding area it is presented a production chain of varied models that is produced daily, whereby there is evidence of imbalance and nonconformities in the spot welding production line of the Motor Wingle 7 Great Wall model, as well as the delivery delay of the finished product at the end of the entire production line, prior to the relevance of the production plan system, the availability of the resources used in the process was not fully known, since in this way it justifies defective products such as weld openings, blows, scratches, as well as the lack of operational knowledge. The present research project aimed "to standardize the welding process of the Motor Wingle 7 Great Wall model in the Ciauto Cia. Ltda vehicle assembly plant because of the reproduction and repeatability of the process, the inductive and bibliographic method was applied, as well as the observation technique, from which it was obtained as a result: the identification and correct use of the available resources by means of the elaboration of the work instructions adjusting to the control plan of the brand and model as well as the application of the study of times and line balance, the benefit is deducted in both parts at the time of decision making since it is possible to comply with the production plan of 16 units per day with the lower use of labor resources being 4 necessary operators, as well as the increase in production of 18 units by maintaining the current amount of 5 operators together with the graphic interpretation of the route and distribution of the resource over the entire standard process hoisted for continuous improvement.